The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Remembering and Forgetting Early Childhood 2020
DOI: 10.4324/9781003030102-2
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the reported age in earliest memories

Abstract: Previous work suggests that the estimated age in adults' earliest autobiographical memories depends on age information implied by the experimental context [e.g., Kingo, O. S., Bohn, A., & Krøjgaard, P. (2013). Warm-up questions on early childhood memories affect the reported age of earliest memories in late adolescence. Memory, 21(2), 280-284.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…One of our goals was to see if we could prime a landmark mindset in the Priming cohort by asking them about the presence and dates of a number of potential landmark events prior to memory recall. Priming varying mindsets has been effective in other research (Bargh et al, 1996; Dijksterhuis & van Knippenberg, 1998; Kingo et al, 2013; Wang & Ross, 2005; Wessel et al, 2017) but to our knowledge has not been used before in an attempt to manipulate strategy use for dating early memories. Landmarks are significant events whose dates are known, and which also can function as chronological reference points or “time tags” for dating other events (Friedman, 1993; Shum, 1998).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…One of our goals was to see if we could prime a landmark mindset in the Priming cohort by asking them about the presence and dates of a number of potential landmark events prior to memory recall. Priming varying mindsets has been effective in other research (Bargh et al, 1996; Dijksterhuis & van Knippenberg, 1998; Kingo et al, 2013; Wang & Ross, 2005; Wessel et al, 2017) but to our knowledge has not been used before in an attempt to manipulate strategy use for dating early memories. Landmarks are significant events whose dates are known, and which also can function as chronological reference points or “time tags” for dating other events (Friedman, 1993; Shum, 1998).…”
Section: Discussionmentioning
confidence: 83%
“…Wang and Ross (2005) found that participants recalled more self‐focused memories after their autonomous self‐goals were made salient and more socially oriented memories after their relational self‐goals were made salient. Of more relevance to the current's study focus on earliest memories, researchers have primed high school or adult participants with memories from younger versus older ages and then asked participants to describe their own earliest memories (Kingo et al, 2013; Wessel et al, 2017). Those participants primed by hearing examples of the earlier memories in turn dated their own earliest memories from a younger age.…”
Section: Priming Landmark Strategiesmentioning
confidence: 99%